Dental caries in 0- to 5-year-old Brazilian children: prevalence, severity, and associated factors - SIMONE HELENA FERREIRA, JORGE U. BÉRIA, PAULO FLORIANI KRAMER, ELIANE GERSON FELDENS, & CA (IAPD and Blackwell, 2007)
Dental caries is a public health problem that affects infants and preschoolers throughout the world, leading to pain, chewing difficulties, speech problems, general health disorders, psychological problems, and lower quality of life.